Renewable and non-renewable electricity-growth nexus in Asia: The role of private power plants and oil price threshold effect. (September 2022) - Husaini, Dzul Hadzwan; Lean, Hooi Hooi
Abstract: A common narrative is that growth based on fossil-fuel-based energy source is not as ecologically benign as non-renewable energy. Green energy promotes economic growth in a more environmentally friendly manner. This paper examines the relationship between economic growth and electricity production by public and private power plants in Asia. The development of more private power plants is expected to allow the energy sector to drive greater economic growth. Threshold estimation is used to analyze the relationships between the variables. We employ oil price as the threshold variable. Our sample covers eight selected Asia countries, grouped into ASEAN and non-ASEAN countries. We conclude that the public power plants are driving more economic growth when the oil price is high (oil price > USD 37.89). On the other hand, the private power plants are performing well in triggering economic growth when the oil price is low (oil price < USD 37.89). We recommend that the government improve the efficiency of the grid's transmission system that aims to reduce the transmission and distribution loss. We also recommend the government to offer various incentives to encourage the construction of more private power plants to increase the electricity supply. Highlights: The variation in the nonlinear electricity-growth nexus by public and private power plants is investigated. The public power plants drive more economic growth when the oil price is high. The private power plants perform well when the oil price is low. Renewable electricity has bigger overall economic impact than non-renewable electricity. We recommend incentives to encourage the setup of more private power plants to increase the electricity supply.